Pengaruh Supervisi Akademik dan Budaya Sekolah terhadap Kinerja Guru SMP Se Kecamatan Tersono Kabupaten Batang - Fikria, I'anatul; Abdullah, Ghufron; Soedjono, Soedjono (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The success of teacher performance is largely determined by the success of the principal in managing the teaching and educational staff in the school. The school principal is one component of education that has an influence on improving teacher performance. The school principal is responsible for organizing educational activities, school administration, developing teaching staff, carrying out academic supervision and developing school culture. The aims of this research are (1) to determine the influence of academic superordination on teacher performance (2) to determine the influence of school culture on teacher performance (3) to determine the influence of academic supersidiction and school culture together on the performance of junior high school teachers in Tersono District, Batang Regency. The population of this study were teachers at 7 junior high schools in Tersono District, Batang Regency, totaling 141 people, a sample of 104 teachers selected using proportional random sampling technique at each school. Validity, reliability and descriptive data analysis tests, single regression and multiple regression tests using the SPSS for Windows version 23 program. Research findings: (1) the influence of academic superordination on teacher performance is 88.4% with the regression equation Ŷ = 27,455 + 0.635 X2. (3) the influence of academic superimposition and school culture together on teacher performance is 92.8% with the regression equation Ŷ = 47.159 + 0.304X1 + 0.765X2, Based on the findings above: (1) the principal intensifies the evaluation of supervision results, (2) the principal increases supervision in the main work tasks of teachers, (3) teachers increase involvement in school activities. Keywords: academic supervision, school culture, teacher performance